Anthropometric features associated with frailty in community-dwelling elderly without functional impairment - Ortiz, Pedro J. (2019)
OBJECTIVE. To determine the association between body composition and frailty syndrome in elderly people without functional impairment. METHODS. A cross sectional comparative study was made of a sample of 37 frail and 68 non-frail older adults according to the Fried's diagnostic criteria in an urban community of Lima, who underwent anthropometric and bioelectrical impedance measurements. Chi-square test, ANOVA test and Pearson's correlation test was done to predict frailty probability. RESULTS. Significant lower values in weight, height, body mass index, brachial perimeter, subcutaneous skin-fold, muscular arm circumference, fat mass and fat-free mass were found in frail older adults (p = 0,005). There was no correlate between frailty syndrome and fat mass measured by electric impedance and with muscle mass measured by anthropometry. We found a 9 % increased risk per kilogram of less weight, OR: 0,91 (p = 0,002) and an 11 % increased risk per each additional year of life, OR: 1,11 (p = 0,005). A logistic formula of frailty prediction was created. CONCLUSIONS. Frail older adults have anthropometric differences in relation to non-frail. A greater probability of frailty is associated with increasing age and weight reduction.